Pears, pistachios, pencils and punctuation: Performative encounter and the art of conversation. (1st February 2020) - Foster, Karl; Foster, Kimberley; Mitchell, Victoria
Words, utterance, gesture, mark-making, ink, nut shells, a peach or a stray button prompt material-discursive engagement. Nothing is taken for granted in terms of knowledge or experience other than a belief that such engagement is a practice, revealing of itself. This article proposes and exemplifies an 'apparatus' of such practice, in which the materially embedded and/or physically embodied production of speech, writing, objects and images are intermingled. This practice has evolved through collaboration, within and across successive performative encounters. Through the intra-acting agencies of performative encounter, the material and the verbal are in conversation, questioning the production of knowledge, critically and metaphorically determined as a 'digestive tract of knowing'. A material engagement emerges that is continuously enmeshed, unravelled and revealed as an embodied tract that surfaces as diagram, apparatus or a conjunction of vertices.In this context, words, whether written, spoken, uttered or as yet unsaid, are interior to the practice. Together and continuously, their shared and formative meanings are mobile, never settling, always productive. Whether critically informed or invented on the spur of the moment, words (including the writing of this article) act as material-discursive fabric. This research-in-action is evident both in the operative engagement and in the subsequent opening of the practice to others, whether as display, text, performance or dialogic example.